Eureka - Wellington, Jo; Garner, Simon; Classroom Video (Australia : Classroom Video, 2009)
This Australian-made, curriculum fit program is an in-depth examination of the eureka stockade - one of white Australia's early defining political and social events
Title from container
Executive producer, Simon Garner
Voice over: Ron Hedgcock
DVD Format
Keywords: Revolutions -- Australia -- Ballarat (Vic.) -- History -- 19th century; Eureka Stockade (Ballarat, Vic.) -- History; Ballarat (Vic.) -- History -- 19th century; Ballarat (Vic.) -- Social conditions -- 19th century